2013
DOI: 10.1186/1743-422x-10-329
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional profiling of feline infectious peritonitis virus infection in CRFK cells and in PBMCs from FIP diagnosed cats

Abstract: BackgroundFeline Infectious Peritonitis (FIP) is a lethal systemic disease, caused by the FIP Virus (FIPV); a virulent mutant of Feline Enteric Coronavirus (FECV). Currently, the viruses virulence determinants and host gene expressions during FIPV infection are not fully understood.MethodsRNA sequencing of Crandell Rees Feline Kidney (CRFK) cells, infected with FIPV strain 79–1146 at 3 hours post infection (h.p.i), were sequenced using the Illumina next generation sequencing approach. Bioinformatic’s analysis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 37 publications
2
22
0
Order By: Relevance
“…CCL8, CXCL10, and CCL17), genes related to innate immune responses (e.g. PHF11 and IRF1), and some genes like MX1 also showed significant up regulation ( Supplementary Table 1), confirming the findings from previous study by Harun and his colleagues [22].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…CCL8, CXCL10, and CCL17), genes related to innate immune responses (e.g. PHF11 and IRF1), and some genes like MX1 also showed significant up regulation ( Supplementary Table 1), confirming the findings from previous study by Harun and his colleagues [22].…”
Section: Discussionsupporting
confidence: 88%
“…Transcriptome analysis of FIPV infected cells showed that the virus probably increase the inflammation through the chemokine and cytokine signaling pathways, Wnt signaling, Cadherin signaling, to name but a few (Tables 3, 4, 5). After 9 hpi, this virus could significant deregulate 4526 genes, which is much higher than 96 genes at 3 hpi according to a previous study by Harun et al [22]. In addition, the expression of some of the ISG genes (e.g.…”
Section: Discussionmentioning
confidence: 77%
“…In the present study, gene expression for all three pyrogenic cytokines (IL-1b, IL-6 and TNF-a) was upregulated in the MLNs in FIP, as well as that for IL-15 (a stimulator of lymphocyte proliferation). We also found significantly higher transcription levels for the monocyte-recruiting chemokines CXCL10 and CCL8, which have both been found to be upregulated in CrandelleRees feline kidney cells after in vitro FCoV infection (Harun et al, 2013), indicating a mechanism of monocyte recruitment as a direct viral effect. Our results confirm their relevance in vivo, with recruitment of monocytes as the infected cell type being a potential amplifying step that is worthy of further investigation.…”
Section: Discussionsupporting
confidence: 51%
“…One of the newest approaches to studying immune responses involves transcriptional profiling, wherein the various cellular mRNAs triggered by a viral infection can be monitored for up-or downregulation. Harun et al (2013) demonstrated the feasibility of such an approach using CRfk cells exposed to FIPV WSU-79-1146 for 3 h. They were able to detect 18,899 of the 19,046 annotated feline genes. Based on results from their culture studies and Kal's Z test, 44 genes were upregulated, 61 genes were not affected by virus infection and the remaining genes were down-regulated.…”
Section: Cytokines and Feline Infectious Peritonitismentioning
confidence: 93%